The Value of Money In Scott Fitzgerald The Great Gatsby - Sumantri, Noel; Maukar, Merlin; Andries, Fivy (Program Studi Pendidikan Bahasa Inggris, 2025)
The tittle of this research is the Value of Money in Scott Fitzgerald The Great Gatsby , The problem to be discussed is how the uniqueness and peculiarity The Great Gatsby novel , this research used descriptive qualitative methods , because the literary work itself is a description of human life in society , in this case , after analyzing the data , the writer then provided a description about the American dream in the novel , the writer chooses passage or quotes from the novel that are related to the research topic , that indicate the “Value” of money in The Great Gatsby , it is expected to be the reference for those who want to conduct similar studies in the future , and acknowledge the reader about certain issue in a novel that might be found in our daily life